The Effect of Implementing the Cooperative Integrated Reading and Composition (Circ) Model Using the Let’s Read Media on Improving Reading Comprehension Skills Among Elementary School Students - Miana Syifa; Indah Nurmahanani; Wina Mustikaati (Lembaga Bale Literasi, 2026)
This study was motivated by the low reading comprehension skills of fourth-grade elementary school students, particularly their difficulty in grasping the content of texts, which is attributed to teaching methods that remain teacher-centered and the lack of innovative media. This study aims to determine the effect of implementing the Cooperative Integrated Reading and Composition (CIRC) model assisted by the Let's Read media on students' reading comprehension skills, and to compare the improvement in reading comprehension between students who received the CIRC model assisted by Let's Read and those who received the Student Teams Achievement Division (STAD) model. This study employed a quantitative approach using a quasi-experimental method and a non-equivalent control group design. The study population consisted of all fourth-grade students at SDN 2 Nagri Kaler, with a sample of 40 students divided into an experimental class and a control class. The results indicate that the implementation of the CIRC model supported by the Let's Read media has a significant effect on students' reading comprehension skills, with a contribution of 54.8% based on the coefficient of determination test. Thus, the CIRC learning model supported by the Let's Read media is effective in improving the reading comprehension skills of elementary school students.